The sign of unilateral neck semispinalis capitis muscle atrophy in patients with chronic non-specific neck pain - Rezasoltani, Asghar; Ahmadipoor, Alireza; Khademi-Kalantari, Khosro; Javanshir, Khodabakhsh (Journal of back and musculoskeletal rehabilitation, 2012)
Background and objectives: Neck muscles have a major role in normal stability and mobility of cervical spine in healthy subjects. Weakness and related atrophy of these muscles may be a causative factor in cervical pain among office workers. The aim of this study was to compare the size and asymmetry of the neck semispinalis capitis muscle (SECM) between a group of female office workers with unilateral chronic non-specific neck pain (CNNP) and a group of healthy control subjects. Material and method: Twenty female office workers (10 patients with unilateral CNNP and 10 healthy subjects) participated in this study. The right and left SECM sizes, anterior posterior dimension (APD) and lateral dimension (LD) were measured by an ultrasonography apparatus. The size of SECM was calculated as APD × LD. Results: The SECM size and the ratio of the size to body weight in patients were less than that of controls ( P < 0.05 , P < 0.001 ). The size of SECM was also smaller in affected side than unaffected side in patients group ( P < 0.05 ). Between sides asymmetry of SECM size was higher in patients than that of controls ( P < 0.001 ). The mean APD of SECM of patients was less than that of controls ( P < 0.01 ). There was not significant difference in LD between two groups. Conclusions: Neck SECM size and asymmetry measurements and the ratio of SECM size to body weight as well as APD appeared to be useful parameters to detect neck muscle atrophy in patients with CNNP.